Wide dispersal and deposition of distal tephra during the Pleistocene 'Campanian Ignimbrite/Y5' eruption, Italy - Pyle, D; Ricketts, G; Margari, V; van Andela, T; Sinitsyn, A; Praslov, N; Lisitsyn, S (2006)
A trachytic volcanic ash layer is widely distributed across south-western Russia, where it is found both in well-characterised archaeological contexts close to the Don River (the Paleolithic sites of Kostenki-Borschevo (51.4°N, 39.0°E), and in undisturbed geological contexts. This ash layer has all of the characteristics of a distal tephra fall deposit: it is fine grained and unimodal with a grain size of 60-170 μm, dominated by strongly elongate glass shard fragments. Chemical analysis confirms that this ash layer is a distal equivalent of the deposits of the ca 39.3 ka Campanian Ignimbrite eruption of the Phlegrean Fields, Italy, and correlates with the widely recognised Y5 ash layer in marine cores in the south-eastern Mediterranean. This work shows that ash particles can be dispersed over considerable distances (>2500 km) and areas (>1.5-3×106 km2) during large-magnitude explosive eruptions. The volume of the products associated with this event (31-50 km3 of magma erupted as fallout tephra, and a total volume of 105-210 km3 of magma, or 2.5-5×1014 kg) confirms the Campanian Ignimbrite/Y5 eruption as the most significant known volcanic eruption in Europe of the past 100 ka. This correlation places tight constraints on the absolute ages of a number of important archaeological horizons in southern Russia. © 2006 Elsevier Ltd. All rights reserved.